Strategy of Modulating Nonradiative Decay for Approaching Efficient Thermally Activated Delayed Fluorescent Emitters - Lei, Jian; Chang, Che-Wei; Chen, Yi-Kuan; Chou, Pang-Yu; Hsu, Liang-Yan; Wu, Tien-Lin; Cheng, Chien-Hong (Journal of physical chemistry. C, 2024)
The photoluminescence quantum yield (PLQY) of an emitter reflects the extent of the nonradiative process and significantly influences the performance of the electroluminescent devices. This study presents a new strategy for designing thermally activated delayed fluorescence (TADF) materials based on suppressing nonradiative decay. The substituents and their positions can modulate exciton behavior in a molecule. We modified the diboraanthranene framework with various alkyl substituents as models to explore the strategy for designing donor–acceptor–donor (D–A–D)-type TADF emitters. Experimental results and theoretical simulations indicate that suppressing nonradiative decay can enhance PLQYs and the delayed component (Φd) of PLQY. Based on the theory of nonradiative decay, our findings suggest that the local C–H stretching modes originating from the alkyl groups are the main contributors to the nonradiative decay rates of the first excited singlet state (k nr,S). Notably, our simulations demonstrate that the PLQYs of the five emitters are increased by alkyl deuteration and can be nearly optimized to 100% through perdeuteration. MECzDBA- and EECzDBA-based green organic light-emitting diodes (OLEDs) achieve superior external quantum efficiencies of 29.4 and 28.6%, respectively, with reduced efficiency roll-off of only 5.1 and 5.2% at 1000 cd m–2. The outcomes from our study suggest a molecular design strategy that successfully counteracts the nonradiative decay in TADF materials, providing a new direction for creating high-efficiency organic emitters.